Models for Measuring E-Learning Success in Universities: A Literature Review - Iuliana DOROBAT (SCORTA) (Informatică economică, 2014)
It is obvious that in the Internet era the higher education institutions (HEIs) must innovate the services they offer by integrating ICT (Information and Communication Technology) in the learning process. According to the theoreticians and practitioners insights in the matter, the e-learning systems offer many advantages and compensate the weaknesses of the traditional learning methods. In consequence, it emerged the need for developing a model that measures the success of the e-learning systems. This paper presents results of the research conducted in order to develop a comprehensive model for measuring e-learning system success in universi-ties.